Recurrent bioprosthetic tricuspid valve endocarditis with valve stenosis and septic pulmonary embolism - Tomasz Czerski; Szymon Jaszczur; Alicja Borowska; Krzysztof Kuśmierski (Folia Cardiologica)
INTRODUCTION: Severe bioprosthetic tricuspid valve stenosis with pulmonary embolism is an extremely rare complication of recurrent infective endocarditis (IE) in intravenous drug abuse patients. CASE SUMMARY: We present a case of a 31-year-old man, addicted to alcohol and drugs. He was admitted with symptoms of ineffectively treated infection. Eight months prior, he underwent a tricuspid valve replacement due to active endocarditis. Echocardiography showed mobile vegetations attached to leaflets of the bioprosthetic tricuspid valve and severe stenosis without regurgitation, complicated by multiple bilateral septic pulmonary emboli. First-line antibiotics and heparin therapy with psychotherapy and rehabilitation support were effective. Blood cultures grew methicillin-resistant Staphylococcus aureus. The subsequent three hospitalizations were with recurrent infection and further bioprosthesis stenosis and, unfortunately, positive narco-tests, which was the reason for the difference of the surgery. After prolonged antibiotic treatment and mental stabilization, successful reoperation was performed without complications. DISCUSSION: Among iv-drug-addicted patients after tricuspid valve implantation, recurrent endocarditis occurs in approximately one-third of cases, and extremely rarely as valvular stenosis. The most common pathogen of prosthetic valve endocarditis is coagulase-negative Staphylococcus. Tricuspid valve endocarditis can lead to septic pulmonary embolism therapy, which should be individualized in every patient. Repeat valve surgery in recurrent endocarditis drug-addicted patients requires careful ethical and clinical consideration due to possible serious complications; for example, recurrent infection and recidivism. There is a need for straightforward guidelines, especially for patients with reinfections of bioprosthetic valves. A multidisciplinary approach is recommended.